Preparation method of layered carbon-silicon negative electrode material
By modifying layered micron silicon and using carbon coating technology, a carbon silicon negative electrode material with high cycle stability and conductivity was prepared, which solved the problem of large volume expansion and impedance of silicon-based negative electrode materials during electrochemical cycles, and achieved commercial applications with high specific capacity and low cost.
Patent Information
- Application Number
- CN202411998352.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-18
AI Technical Summary
The silicon-based anode material has a large volume expansion and large impedance during electrochemical cycle, which leads to attenuation and even failure of material properties. The preparation process of existing nanosilicon materials is complex and has serious environmental pollution, making it difficult to apply on a large scale on a commercial basis.
By modifying layered micron silicon, using carbon coating technology, combined with high temperature carbonization treatment, a carbon silicon negative electrode material with high cycle stability and conductivity was prepared. This method utilizes the properties of two-dimensional layered silicon to reduce the volume expansion effect and improves the conductivity of the material through carbon coating.
The high specific capacity and high cycle stability of silicon-based negative electrode materials are achieved, which reduces the failure problems caused by volume expansion and reduces the preparation cost, making them suitable for large-scale commercial applications.
Smart Images

Figure CN119852359A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium ion batteries, and in particular to a method for preparing a layered carbon-silicon negative electrode material. Background Art
[0002] Lithium-ion batteries have long been considered an efficient and convenient energy storage device. However, the low specific capacity of commercially available graphite anodes limits their large-scale application in high-energy-density lithium-ion batteries. Among the many known anode materials, silicon has a specific capacity of up to 4200mAh / g, a low discharge voltage and lithium-ion diffusion barrier, and a large reserve in the earth's crust. It is one of the most promising anode materials for lithium-ion batteries. However, the volume expansion effect and high impedance of silicon anodes during the electrochemical cycle can easily cause material performance degradation or even failure.
[0003] At present, the mainstream strategy for the volume expansion problem of silicon negative electrode materials is to nanosize silicon particles and use Si nano-microspheres and ordered mesoporous Si materials in structural design. These solutions can solve the volume expansion problem of silicon negative electrode materials to a certain extent, but the chemical synthesis of nano silicon particles is usually accompanied by great environmental pollution, and the template method preparation process is complex and costly, making it difficult to apply them on a large scale commercially.
[0004] To this end, there is an urgent need for a solution that enables silicon-based negative electrode materials to have both conductivity and a certain buffer expansion capacity, so that they can have high specific capacity and high cycle stability, while reducing costs. Summary of the invention
[0005] In view of this, the present application provides a method for preparing a carbon-silicon negative electrode with high cycle stability from layered micron silicon. It aims to improve the problem of poor cycle stability of existing silicon-based negative electrode materials by modifying layered micron silicon. This scheme uses layered silicon as the raw material. Since the two-dimensional material has a very small scale in a certain direction, it can effectively transfer mass and conduct electricity. In addition, the cost of micron silicon raw materials is low, and the production process is simple and mature, and it is expected to be promoted on a large scale. Combined with carbon coating, it can effectively alleviate the problem of volume expansion of silicon-based materials and increase the conductivity of the material. The silicon-based negative electrode material prepared by this scheme has high specific capacity, strong consistency between batches, low cost, and exhibits excellent cycle stability.
[0006] The present invention provides a method for preparing a layered carbon-silicon negative electrode material, which comprises the following steps:
[0007] (1) washing, filtering and drying the layered micron silicon sample;
[0008] (2) soaking, cleaning and drying the sample obtained in step (1);
[0009] (3) adding the organic carbon source to the buffer solution of the sample obtained in step (2), and obtaining a sample coated with the organic carbon source after reaction, washing and drying;
[0010] (4) Placing the sample obtained in step (3) in a tube furnace, and subjecting it to high-temperature carbonization treatment to obtain a carbon-coated micron silicon-based negative electrode material.
[0011] In the present invention, in step (1), the cleaning can be performed in a conventional manner in the art, such as acetone cleaning, ethanol cleaning or deionized water cleaning, etc. Preferably, the cleaning step is to ultrasonically clean the layered micron silicon sample in acetone, and then clean it with anhydrous ethanol and deionized water.
[0012] In the present invention, the layered micron silicon sample in step (1) is silicon powder in the shape of a lamella; the lamella shape means that the size is smaller in a certain direction; the micron silicon means that the size in one direction reaches 1 μm.
[0013] In the present invention, the layered micron silicon sample in step (1) may be synthesized by chemical methods or obtained by mechanically grinding and crushing large silicon blocks.
[0014] In the present invention, the thickness dimension of the layered micron silicon sample in step (1) may be 0.01-1 μm, preferably 0.01-0.05 μm. The lateral dimension of the layered micron silicon sample may be 0.1-20 μm, preferably 0.5-10 μm.
[0015] In the present invention, the cleaning time in step (1) is 5 to 60 minutes, preferably 20 to 30 minutes.
[0016] In the present invention, the drying time in step (1) is 3 to 20 hours, preferably 5 to 12 hours, and the drying temperature is 50 to 100°C, preferably 60 to 80°C.
[0017] In the present invention, in step (2), the soaking method can be conventional in the art, such as soaking in dilute nitric acid.
[0018] The mass fraction of the dilute nitric acid in step (2) is 0.1% to 10%, preferably 0.5 to 2%. The soaking time of the dilute nitric acid is 30 min to 3 h, preferably 30 min to 1 h. The mass ratio of the dilute nitric acid solution to the sample is 5000:1 to 5:1, preferably 5000:1 to 500:1.
[0019] In the present invention, the drying temperature in step (2) is 50 to 90° C., preferably 60 to 80° C. The drying time is 5 h to 48 h, preferably 5 to 12 h.
[0020] In the present invention, step (3) is specifically as follows: placing the sample obtained by the treatment in step (2) into a prepared buffer solution, then adding 1 / 10 to 1 / 2 of an organic carbon source, preferably 1 / 5 to 1 / 3; after ultrasonic stirring, adding the remaining carbon source into the system. After reacting at a temperature of 10 to 80° C. for 5 to 30 hours, the sample is taken out, washed, dried and set aside.
[0021] In the present invention, the buffer solution in step (3) can be one or more of neutral buffer systems such as NaCl / tris-bis, Na2HPO4 / NaH2PO4, etc., preferably NaCl / tris-bis; the pH control range is 4 to 10, preferably 6 to 8; the mass ratio of the buffer solution to silicon powder is 5000:1 to 5:1, preferably 5000:1 to 500:1.
[0022] In the present invention, the carbon source in step (3) can be one or more of tannic acid, glucose, etc., preferably tannic acid. The mass ratio of the organic carbon source to silicon powder is 1:5 to 5:1, preferably 1:2 to 2:1.
[0023] In the present invention, the volume of the tubular furnace described in step (4) is 3 dm 3 ~15dm 3 , preferably 5 to 10 dm 3 ; The inert gas is one or more of Ar and N2. The pressure in the tube furnace after vacuuming is 0.001 MPa-0.05 MPa, preferably 0.001-0.01 MPa; the protective gas flow rate is 10-100 ml / min, preferably 50-80 ml / min.
[0024] In the present invention, the high temperature carbonization in step (4) is specifically:
[0025] First, the temperature is raised to 200-500°C, preferably 300-500°C, at a heating rate of 1-5°C / min, preferably 1-2°C / min; and kept warm for 1-5h, preferably 1-3h.
[0026] Then, the temperature is raised to 500-900° C., preferably 600-800° C., at a heating rate of 3-8° C. / min, preferably 4-6° C. / min; and kept at this temperature for 1-5 h, preferably 1-3 h.
[0027] Finally, the temperature is lowered to room temperature at a cooling rate of 5 to 10°C / min, preferably 5 to 8°C / min.
[0028] Technical Effects
[0029] The present invention relates to a method for preparing a carbon silicon negative electrode with high cycle stability from layered micron silicon, and belongs to the technical field of silicon-based negative electrodes for lithium ion batteries. The present invention first washes the layered silicon and puts it into a nitric acid solution for surface treatment, and then filters it after soaking it for a period of time, and then washes it with clean water and puts it into a vacuum oven for drying. The treated sample is placed in a buffer solution and an organic carbon source to coat the organic matter, and then taken out, washed, dried, and placed in a tubular furnace for carbonization. The coated organic matter is first slowly dehydrated and expanded by a step-by-step heating method, and then the temperature is quickly raised to carbonize and fix it. Its microstructure is a uniform nanosheet, which helps to increase the contact area between the electrolyte and the electrode and improve the deintercalation efficiency of lithium ions. The present invention proposes to use lamellar micron silicon as a raw material to prepare a negative electrode material for lithium ion batteries, which is suitable for mass production of stable silicon-based negative electrodes. The prepared electrode material has good uniformity, strong consistency between batches, simple operation, low cost, and is easy for mass industrial production.
[0030] Compared with the prior art, the present invention has obvious advantages in the following aspects:
[0031] (1) High cycle stability negative electrode.
[0032] The biggest problem with silicon negative electrodes at present is that the volume expands during the charge and discharge process, which causes the material to pulverize and fail. The two-dimensional layered material is smaller in the thickness direction. During the charge and discharge process, the volume expansion effect of silicon in a certain thickness direction can be much lower than the lateral size, greatly reducing the failure problem caused by expansion; at the same time, carbon coating technology is used to further inhibit the expansion effect and increase conductivity. The silicon-carbon negative electrode prepared with layered micron silicon can stably operate for more than 500 cycles at a current density of 1A / g and maintain a specific capacity of more than 80%. The specific capacity is far greater than the current commercial graphite negative electrode, and has the potential for further promotion.
[0033] (2) The raw materials are widely available and of low cost.
[0034] The present invention uses micron silicon as raw material, which has a cost difference of several orders of magnitude compared to nano silicon, and breaks the limitation of traditional nanoparticles as silicon negative electrode in material design. The operation process is simple, the equipment requirements are low, the carbon source is selected from cheap organic matter such as tannic acid and glucose, and the raw materials are cheap and easy to obtain, which has cost advantages. Under the condition of ensuring that the performance is not significantly reduced, the cost of silicon raw materials can be reduced to 30% of the original.
[0035] (3) Can be prepared in large quantities.
[0036] Micron silicon has a low specific surface energy, and the powder is easier to disperse in the solution than nano powder. The organic solvent can fully contact the surface of the silicon powder to promote the carbon coating process, which is beneficial to the preparation of larger batches of silicon negative electrode materials within a fixed volume. The operation is simple, the repeatability is strong, the uniformity within the batch is good, and the consistency between batches is easy to ensure. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 X-ray diffraction patterns (XRD) of layered silicon, silicon-carbon anode of Example 1 and Example 2;
[0038] Figure 2 This is a scanning electron microscope (SEM) image of layered silicon;
[0039] Figure 3 This is a scanning electron microscope (SEM) image of the layered silicon-carbon negative electrode material prepared in Example 1;
[0040] Figure 4 This is a scanning electron microscope (SEM) image of the electrode sheet prepared in Example 1;
[0041] Figure 5 This is a test diagram of the cycle performance of the electrode sheet prepared in Example 1 after being assembled into a half-cell;
[0042] Figure 6 This is the TEM image of the layered silicon-carbon negative electrode material prepared in Example 1. DETAILED DESCRIPTION
[0043] The following describes several preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.
[0045] The technical solution of the present invention is described below in conjunction with specific embodiments of the present invention.
[0046] Example 1
[0047] (1) 200 mg of layered micron silicon sample was placed in 100 mL of acetone for ultrasonic cleaning, filtered, cleaned with anhydrous ethanol and deionized water, filtered, and dried at 60°C overnight for use.
[0048] (2) Soak the cleaned silicon powder sample in step (1) in a 1% by mass dilute nitric acid solution for 1 hour, take it out and wash it with clean water, filter it, and bake it at 60° C. for 6 hours before use.
[0049] (3) The sample obtained in step (2) was immersed in a buffer solution, wherein the buffer solution was 200 mL of a NaCl-tris buffer system, and stirred for 0.5 h.
[0050] (4) Then, 100 mg of tannic acid was added to the system of step (3), and after ultrasonic stirring for 0.5 h, another 100 mg of tannic acid was added to the system. After reacting at 25° C. for 24 h, the mixture was filtered and washed with clean water several times, and dried at 60° C. for 6 h before use.
[0051] (5) The sample of step (4) is placed in a tube furnace, and the inlet of the tube furnace is connected to Ar inert gas. The tube furnace is first evacuated to a pressure of 0.001 MPa, and then Ar protective gas is introduced at a protective gas flow rate of 71 ml / min. After setting the following high-temperature carbonization treatment procedure, a carbon-coated micron silicon-based negative electrode material is obtained by reaction.
[0052] First, increase the temperature to 400°C at a heating rate of 1°C / min and keep it for 2h;
[0053] Then, the temperature was raised to 800°C at a heating rate of 5°C / min and kept at that temperature for 3 h.
[0054] Finally, the temperature was lowered to room temperature at a cooling rate of 10°C / min.
[0055] Example 2
[0056] (1) 200 mg of layered micron silicon sample was placed in 100 mL of acetone for ultrasonic cleaning, filtered, cleaned with anhydrous ethanol and deionized water, filtered, and dried at 80°C overnight for use.
[0057] (2) Soak the cleaned silicon powder sample in step (1) in a 2% by mass dilute nitric acid solution for 1 hour, take it out and wash it with clean water, filter it, and bake it at 80° C. for 6 hours before use.
[0058] (3) The sample obtained in step (2) was immersed in a buffer solution, wherein the buffer solution was 200 mL of a NaCl-tris buffer system, and stirred for 0.5 h.
[0059] (4) Then, 200 mg of tannic acid was added to the system of step (3), and after ultrasonic stirring for 0.5 h, another 200 mg of tannic acid was added to the system. After reacting at 25° C. for 24 h, the mixture was filtered and washed with clean water several times, and dried at 60° C. for 6 h before use.
[0060] (5) The sample of step (4) is placed in a tube furnace, and the inlet of the tube furnace is connected to Ar inert gas. The tube furnace is first evacuated to a pressure of 0.001 MPa, and then Ar protective gas is introduced at a protective gas flow rate of 71 ml / min. After setting the following high-temperature carbonization treatment procedure, a carbon-coated micron silicon-based negative electrode material is obtained by reaction.
[0061] First, increase the temperature to 500°C at a rate of 2°C / min and keep it for 2h;
[0062] Then, the temperature was raised to 800°C at a heating rate of 5°C / min and kept at that temperature for 5 h.
[0063] Finally, the temperature was lowered to room temperature at a cooling rate of 5°C / min.
[0064] Effect Example
[0065] The layered silicon, the silicon-based negative electrode materials of Example 1 and Example 2 were subjected to X-ray diffraction test and the following results were obtained: Figure 1 The diagram shown; Figure 1 It shows that silicon is the main crystalline phase and carbon exists in an amorphous form.
[0066] The layered silicon was subjected to SEM testing, such as Figure 2 As shown, the morphological characteristics of layered silicon are displayed, with a lateral size of micrometer level, approximately 2 to 10 μm, and a thickness of less than 50 nm.
[0067] The carbon-coated micron silicon-based negative electrode material prepared in Example 1 and the electrode sheet prepared therefrom were subjected to scanning electron microscope (SEM) testing. Figure 3 and 4 As shown, Figure 3 It shows the morphology of the layered silicon after being coated with a carbon layer; Figure 4 It shows that the surface composition of the prepared electrode sheet is uniform. Figure 6 Shown is a TEM image of the layered silicon-carbon negative electrode material prepared in Example 1. It can be seen from the figure that the dark part is layered silicon, which is tightly coated by the gray carbon layer.
[0068] The materials prepared in Example 1 were finally assembled into a half-cell and its cycle performance was tested. Figure 5 The prepared negative electrode sheet was assembled into a half-cell and operated for 500 cycles at a current density of 1 A / g, with a capacity retention rate of 90%.
[0069] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments or to replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
[0070] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a layered carbon-silicon negative electrode material, characterized in that: It includes the following steps: (1) washing, filtering and drying the layered micron silicon sample; (2) soaking, cleaning and drying the sample obtained in step (1); (3) adding the organic carbon source to the buffer solution of the sample obtained in step (2), and obtaining a sample coated with the organic carbon source after reaction, washing and drying; (4) Placing the sample obtained in step (3) in a tube furnace, and subjecting it to high-temperature carbonization treatment to obtain a carbon-coated micron silicon-based negative electrode material.
2. The method for preparing a layered carbon-silicon negative electrode material according to claim 1, characterized in that: The thickness dimension of the layered micron silicon sample in step (1) is 0.01 to 1 μm, and the lateral dimension of the layered micron silicon sample is 0.1 to 20 μm.
3. The method for preparing the layered carbon-silicon negative electrode material according to claim 2, characterized in that: The thickness dimension of the layered micron silicon sample in step (1) is 0.01 to 0.05 μm, and the lateral dimension of the layered micron silicon sample is 0.5 to 10 μm.
4. The method for preparing a layered carbon-silicon negative electrode material according to claim 1, characterized in that: The cleaning time in step (1) is 5 to 60 minutes; the drying time is 3 to 20 hours; and the drying temperature is 50 to 100°C.
5. The method for preparing a layered carbon-silicon negative electrode material according to claim 1, characterized in that: The soaking method in step (2) is dilute nitric acid soaking; the mass fraction of the dilute nitric acid is 0.1% to 10%.
6. The method for preparing the layered carbon-silicon negative electrode material according to claim 5, characterized in that: The soaking time of the dilute nitric acid in step (2) is 30 minutes to 3 hours; the mass ratio of the dilute nitric acid solution to the sample is 5000:1 to 5:1; The drying temperature in step (2) is 50-90° C. and the drying time is 5 h to 48 h.
7. The method for preparing a layered carbon-silicon negative electrode material according to claim 1, characterized in that: Step (3) is specifically as follows: placing the sample obtained in step (2) into a prepared buffer solution, then adding 1 / 10 to 1 / 2 of an organic carbon source, and then adding the remaining carbon source into the system.
8. The method for preparing a layered carbon-silicon negative electrode material according to claim 1, characterized in that: The organic carbon source in step (3) is tannic acid and / or glucose.
9. The method for preparing a layered carbon-silicon negative electrode material according to claim 1, characterized in that: In step (3), the mass ratio of the organic carbon source to the layered micron silicon sample is 1:5 to 5:
1.
10. The method for preparing a layered carbon-silicon negative electrode material according to claim 1, characterized in that: The high temperature carbonization treatment in step (4) is specifically as follows: First, increase the temperature to 200-500°C at a heating rate of 1-5°C / min and keep warm for 1-5h; Then, the temperature is raised to 500-900°C at a heating rate of 3-8°C / min and kept at this temperature for 1-5h; Finally, cool down to room temperature at a cooling rate of 5-10℃ / min.
Citation Information
Patent Citations
Silicon carbon composite material for lithium ion battery cathode, and preparation method of composite material
CN104752698A
Silicon-carbon composite material and preparation method thereof, negative plate and lithium ion secondary battery
CN112736232A
Surface nitriding modified lithium battery silicon-based negative electrode material and preparation method thereof
CN119160895A
Negative electrode active material for lithium ion secondary batteries, manufacturing method thereof, and lithium ion secondary battery
JP2017084684A
Anode material composition for a lithium ion battery
US20160344018A1